Hubungan Pendidikan Ibu Dengan Perilaku Ibu Dalam Pencarian Pengobatan Balita Pneumonia Di Kabupaten Purworejo - Tri Peni (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2010)
Pneumonia remains a serious problem as it is one of major causes in under-five children’s morbidity and mortality worldwide; however, it gets little concern, including in Indonesia. In Purworejo District, the finding coverage of this disease in community health centers is still low (3.7%), due to the fact that it may be caused by inappropriate care seeking behavior. This study was conducted to know the relationship between mother’s educational level and care seeking behavior for under-five children’s pneumonia. This was an observational study with cross sectional design. The study was conducted in community health centers and hospital in Purworejo District. The subjects were 126 mothers with pneumonia under-five children brought to appointed community health centers and hospital fulfilling inclusion criteria. Independent variable was mothers’ education and dependent variable was mothers’ care seeking behavior for pneumonia under-five children. The study used primary data analyzed by univariable analysis, bivariable with chi-square, and multivariable with logistic regression. Prevalence of bad behavior respondents was 59.52%. Mothers with lower educational level had risk of 2,38 times higher in bad care seeking behavior than those with higher educational level with 95%CI=1,02-5,51. Confounding variable contributing significant influence was economic status and dissemination of information. Mothers’ education is related to care seeking behavior for pneumonia under-five children. Another Factors related to mothers’ care seeking behavior in Purworejo District are economic status and dissemination of information